Analysis of Youth Empowerment Policies in Supporting Sustainable Development in Developing Countries - Andi Thamrin; Laily Ramadhany Can; Musiana Musiana (West Science Interdisciplinary Studies, 2024)
This research aims to analyze policies for youth empowerment in supporting sustainable development in developing countries. Through a literature review method, this study explores key factors influencing the effectiveness of youth empowerment policies, evaluates implemented strategies, and formulates relevant policy recommendations. Findings reveal that access to education and training, poverty alleviation and unemployment, as well as political participation and social engagement are crucial aspects of youth empowerment. Holistic, inclusive, and integrated policies are required to ensure effective and sustainable youth empowerment. Policy recommendations include expanding access to education and training, developing locally-based poverty alleviation programs, and strengthening political participation and social engagement of youth. The implementation of these policies necessitates cross-sectoral and intergenerational collaboration.